The Use (and Abuse) of CDS Spreads During Distress - Spackman, Carolyne (IMF Working Papers; Working Paper ;, 2009)
Credit Default Swap spreads have been used as a leading indicator of distress. Default probabilities can be extracted from CDS spreads, but during distress it is important to take account of the stochastic nature of recovery value. The recent episodes of Landbanski, WAMU and Lehman illustrate that using the industry-standard fixed recovery rate assumption gives default probabilities that are low relative to those extracted from stochastic recovery value as proxied by the cheapest-to-deliver bonds. Financial institutions using fixed rate recovery assumptions could have a false sense of security, and could be faced with outsized losses with potential knock-on effects for other institutions. To ensure effective oversight of financial institutions, and to monitor the stability of the global financial system especially during distress, the stochastic nature of recovery rates needs to be incorporated.